1973
DOI: 10.1002/jlac.197319730708
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocide Diamidine mit vier Ringen in einem oder zwei Ringsystemen

Abstract: )Vgl. die bei Lit.7) angegebenen Ubersichten, dort FuDnotens-l3).Ann. Chem. 760, 37 (1972). Chem. 734, 23 (1970). R = B r o d e r H la: R. R' B r b: R. R' = C N c : R, R' = [C(NH2)2]"Cl0 = Am d: R = H; R' = B r Beirn kurzen Kochen von 3-Acetoxy-5-brornbenzo[b]thiophen 10) rnit iiberschiissigem (3-Brornpheny1)hydrazin in Eisessig erfolgte der bekannte") RingschluR nach dern Prinzip der Fischer schen Indolsynthese12), dessen isoliertes Hauptprodukt als 1 a anzusehen war, nachdern bei derselben Reaktion rnit 3-Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…On substituting imidazolino groups for amidino groups, the antifungal activities of type A compounds generally diminished. This detrimental effect was less pronounced with the more active indoles (6, 4) than with the benzofurans (8,7) or benzothiophenes (17,13). Less disadvantageous was the replacement of the amidino groups by guanidino groups, as shown by 10 and 7 and by 19 and 13.…”
Section: Resultsmentioning
confidence: 98%
“…On substituting imidazolino groups for amidino groups, the antifungal activities of type A compounds generally diminished. This detrimental effect was less pronounced with the more active indoles (6, 4) than with the benzofurans (8,7) or benzothiophenes (17,13). Less disadvantageous was the replacement of the amidino groups by guanidino groups, as shown by 10 and 7 and by 19 and 13.…”
Section: Resultsmentioning
confidence: 98%
“…The bis-benzimidazoles used in the present study were synthesized according to previously described methods (6,9,18,19 Large-scale cultures were cultivated in outside in roller bottles (Bellco Glass, Inc., Vineland, N.J.), which provide a high surface area-to-volume ratio (10). Logarithmically growing trophozoites (2 x 106) were inoculated into each bottle containing approximately 625 ml of medium.…”
Section: Methodsmentioning
confidence: 99%
“…The bis-benzimidazoles used in the present study were synthesized according to previously described methods (6,9,18,19). The purity of the compounds was determined by high-performance liquid chroma-tography, elemental analyses, and nuclear magnetic resonance spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1970s Dann O et al [30][31][32] Tidwell RR et al found that the in vitro anti-trypanosomal activities of bisbenzofuran derivatives against Trypanosoma brucei rhodesiense, and cytotoxicity against mammalian cells depended on the position and the type of cationic substituents as well as the length of the carbon linker between aromatic moieties. As observed in most of the dicationic molecules, the N-substituted congeners were lesser cytotoxic than the unsubstituted diamidines whereas the N-alkylation of cationic fragments reduced the activity of compounds against T. brucei rhodesiense compared to pentamidine.…”
Section: Benzofuran Derivativesmentioning
confidence: 99%